2009
DOI: 10.1128/jb.01517-08
|View full text |Cite
|
Sign up to set email alerts
|

A Regulatory Network Controls Expression of the In Vivo-Expressed HreP Protease of Yersinia enterocolitica

Abstract: The human enteropathogen Yersinia enterocolitica survives and replicates in the lymphoid tissues of its host. Previous in vivo analyses of gene expression revealed that various chromosomal genes are expressed at this stage of infection, but not in vitro. One of these, termed hreP, encodes a protease that is necessary for full virulence of Y. enterocolitica. Using transposon mutagenesis, we identified three genes, pypA, pypB, and pypC, as positive regulators of hreP transcription. PypA is an inner membrane prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(36 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…Our results demonstrate that the pilus is likely important during the intracellular phase of infection, perhaps allowing the bacteria to adhere to the inner surface of the YCV and facilitate the translocation of T3SS effectors across the vacuolar membrane. It should be noted that the regulator of the Yts2 T2SS, PypC, also regulates expression of pypB (59), indicating a clear link between the Tad type IVb pilus and the Yts2 system in bacteria that have been internalized by macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results demonstrate that the pilus is likely important during the intracellular phase of infection, perhaps allowing the bacteria to adhere to the inner surface of the YCV and facilitate the translocation of T3SS effectors across the vacuolar membrane. It should be noted that the regulator of the Yts2 T2SS, PypC, also regulates expression of pypB (59), indicating a clear link between the Tad type IVb pilus and the Yts2 system in bacteria that have been internalized by macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the Yts1 system, the upstream regulator of the Yts2 system, PypC, directly regulates the downstream genes encoding the T2S apparatus (29). Intriguingly, PypC has also been found to positively regulate the genes for the transcriptional regulator pypB, the regulator of the tad locus, and hreP, which encodes a protease required for full virulence of Y. enterocolitica (59,72).…”
Section: Expression Of the Yts1 And Yts2mentioning
confidence: 99%
“…For routine growth, all strains were grown in LuriaBertani (LB) broth or on agar plates at 26°C for Y. enterocolitica or 37°C for E. coli or as otherwise indicated. Antibiotics were used as described previously (38). For the induction of protein expression from the P BAD promoter, bacteria were grown in the presence of 0.1 to 0.2% (wt/vol) arabinose.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous analysis we identified three regulators, termed PypA, PypB, and PypC, in Y. enterocolitica that activate the transcription of the in vivo-expressed hreP gene, encoding a protease necessary for full virulence in the mouse model of yersiniosis (38). Analysis of the organization of the genomic locus around pypB revealed that it is located upstream of a putative operon homologous to the tad locus of A. actinomycetemcomitans.…”
mentioning
confidence: 99%
“…Among these groups of protein, a group of membrane protease proteins (SMc01135, SMc01440, SMc01441, and SMc04459) were identified. Proteases are important components of complex regulatory networks to cope with environmental stress in many organisms (39,42). SMc04459 (FtsH) has previously been identified in nodule bacteria (9).…”
Section: Identification Of Proteins In the Sinorhizobium Sp Bl3 Membmentioning
confidence: 99%